Critical molecular pathways in CLL therapy - Gerardo Ferrer; Emili Montserrat (BMC, 2018)
Abstract Chronic lymphocytic leukemia (CLL), the most frequent type of leukemia in western countries, is characterized by the progressive accumulation in blood, bone marrow and lymphoid tissues of monoclonal B lymphocytes with a characteristic immunophenotype. Despite advances in therapy and improved outcome, in most instances CLL is an incurable disorder. Signaling via the B-cell receptor (BCR), the upregulation of anti-apoptotic proteins, and the cross-talk between CLL cells and microenvironment constitute key factors in the pathogenesis of CLL. Currently, inhibitors of kinases like BTK or PI3K blocking BCR signaling, and molecules that mimic the BH3 domain to compete with BCL-2 are established tools in the treatment of CLL. As the complex biology of CLL is rapidly unfolding, the number of small molecules targeting CLL molecular pathways is increasing and it is likely that they will further improve the outcome of patients with this form of leukemia.